Toplumsal bellek ve sahte-belgesel - Saraç, Fatih (My University, 2020)
arasındaki sınırlarda gelişen ve bu sınırları bulanıklaştıran sahte-belgesel türünün bellek ile ilişkisi incelenmiştir. Bu doğrultuda geçmişin yeniden düzenlenmesi ve inşa edilmesinde Michael Schudson tarafından tanımlanan çarpıtma dinamikleri ile sahte-belgesel kavramı ilişkilendirilerek, türün sahte gerçekliği üretmede belleğe dayalı uygulamalarla örtüşen özellikleri ve bilinçli olarak belleği nasıl çarpıttığı ortaya koyulmuştur. Ayrıca sahte-belgeselin gerçeğe benzer kurmaca yapısının seyir deneyiminde yarattığı karışıklığa ve farklı alımlama biçimlerine bağlı olarak türün seyircide değişken bellek süreçlerini harekete geçirebileceği ve böylece sahte bir bellek oluşturabileceği sonucuna varılmıştır. Bu sayede sahte-belgesel kavramının, türünün ve yapısının bellek ile ilişkisi kurularak formun kavramsal yapısı çözümlenmiştir.

Cinema has been transmitter, transferor and creator of collective memory in reconstructing the past through movies, and acted as a metaphor used in defining memory starting with its emergence. Enabling one to reminisce or forget the past in different dimensions using the urge that the visual imagery brings about, the films has been within the definition of cultural memory as an extension of our collective memory. Reconstruction of the past by means of films has manifested in many forms, both fiction and non-fiction. This study is an examination of the relationship between memory and mock-documentary genre, which take place on the lines between reality and fiction and that blurs these lines. Wihtin this context, by associating the dynamics of distortion described by Michael Schudson in terms of reconstructing and building the past with the concept of mock-documentary, properties coinciding with the memory-based implementations in producing the pseudo-reality and the way that this genre deliberately, twists the memory are exhibited. In addition, this study decudes that the mock-documentary genre, owing to the mixture and diffrent reception types its pseudo-reality fiction structure instills on the audience, can prime variable memory processes for the audience and thus, create a fake memory. This method is able to decode the conception skeleton of the genre by associating the concept, genre and structure of the mock-documentary with memory.
Keywords: Bellek; Bellek ve Sinema; Collective Memory; False Memory; Memory and Cinema; Memory in Mock-Documentary; Mock-Documentary; Motion pictures and television; Sahte Bellek; Sahte-Belgesel; Sahte-Belgeselde Bellek Memory; Sinema ve televizyon; Toplumsal Bellek